Case report: marfan syndrome (MFS) mimicking cutaneous vasculitis - Price-Kuehne, Fiona; Omoyinmi, Ebun; Younes, Maha; Edwards, Matthew; Eleftheriou, Despina; Brogan, Paul (Frontiers in Pediatrics, 2023)
Marfan syndrome (MFS) is an autosomal dominant connective tissue disorder caused by variants in the extracellular microfibril fibrillin (FBN1) gene. Here we report an FBN1 variant in a child with an unusual skin rash mimicking cutaneous vasculitis, and mild aortic root dilatation. The case was complicated by lack of typical skeletal MFS phenotype; and severe needle phobia preventing any blood testing for workup of suspected vasculitis. Therefore inflammatory markers, autoantibody profile and general hematology/biochemistry results were unknown. Diagnosis of MFS was made via genetic testing of a saliva sample alone using a next-generation sequencing (NGS) targeted gene panel designed to screen for monogenic forms of vasculitis and noninflammatory vasculopathic mimics. This revealed the patient was heterozygous for a pathogenic frameshift variant in FBN1; NM_000138, c.1211delC, p.(Pro404Hisfs*44), predicted to cause premature protein truncation leading to loss of function. The variant has not been detected in control populations and has previously been detected in individuals with MFS. This rapid diagnosis significantly impacted the patient management: avoidance of invasive investigations; avoidance of unnecessary immunosuppression; facilitating genetic counselling of the index case and family; and directly informing lifelong monitoring and ongoing treatment for aortic root involvement from MFS. This case further emphasizes the diagnostic utility of NGS early in the diagnostic workup of paediatric patients referred with suspected vasculitis, and we emphasise that MFS can present with cutaneous vasculitic-like features in the absence of the typical Marfanoid skeletal phenotype.